Feasibility of hydrogen production from cellulose and prediction of the product distribution : thermodynamics analysis - Anggoro, Didi Dwi; Udaibah, Wirda; Prasetyaningrum, Aji; Zaki Yamani Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2022)
High carbon emissions, depleting fossil energy reserves have become a global problem. It is necessary to develop renewable energy sources that are environmentally friendly. Hydrogen (H2) is one of the energy sources and carriers that can be developed. This gas can be produced from renewable, sustainable, and economical resource such as biomass that contains cellulose as the main ingredient. This thermodynamic analysis of H2 production from cellulose is necessary as a theoretical study to determine the feasibility of the reaction. The computational thermodynamic was analyzed using Microsoft Excel 2019 and Matlab Program R2013a. Prediction of the equilibrium composition of the substances involved in the reaction was attempted by minimization Gibbs free energy change with Lagrange undetermined multipliers methods. As a result, the value of ΔHr0; ΔSr0 and ΔGr0 are +624,7500 kJ/mol; +2,1491 kJ/mol.K and; -26,1540 kJ/mol, respectively. Analysis of equilibrium constant of this conversion has a large ln K value (> 1). A negative ΔGr0 value and large ln K indicates that the formation of H2 from (C6H10O5)n is plausible and feasible and reaction product formation is strongly favored at equilibrium. The composition of the substances involved at 298 K from the largest to the smallest is CH4 (4.5 mol), H2O (3 mol), CO2 (1.5 mol), H2 (1.28×10-5 mol), HCOOH (5.85×10-10 mol), C6H12O6 (3.72×10-10 mol) and C6H12O5 (1.35×10-10 mol). Interestingly, H2 yield will rise significantly with the increase of reaction temperature. This preliminary study provides an overview of reaction conditions so that H2 production from biomass can be produced maximally.